Ganho genético para produtividade de grãos de soja na região central do Brasil - Mezzalira, Itamara (2017)
Soybean is one of the main products of the Brazilian agribu siness, with a planted area of about 30 million hectares, which provides a great diversity of environments and highlights the importance of breeding programs in obtaining high yielding varieties that are adapted to different growing environments. The success of a breeding program can be measured by the number of cultivars released, the adoption of these cultivars by the producers, the profit obtained with the marketing of seeds and measur ing the genetic gain obtained by the program over the years. In order to measure the genetic gain for soybean grain yield , from maturation group 8 lines, in the Brazilian soybean macro-regions 3 and 4, results obtained in 204 VCU trials between season 2006/07 and 2015/16, were analyzed. The average yield of soybeans in the analyzed period was 3118 kg ha -1 . The majority of experiments had a coefficient of experimental variation lower than 15% and selective accuracy higher than 0.70, demonstrating high quality and experimental precision. The replacement rate of the genotypes over the analyzed years ranged between 29.41% and 77.78%. The annual genetic gain for soybean genotypes of maturation group 8, between season 2006/07 and 2015/16, in the Brazilian soybean macro-regions 3 and 4, was 18.3 kg ha -1 year -1 or 0.59% in relation to the mean of the experiments analyzed. The components of environmental effect, interaction effect and experimental error were significant and of great magnitude, which makes it difficult to obtain the real genetic values of the evaluated genotypes and makes it difficult to calculate the genetic gain. The varieties and lines considered in this study have higher productive potentials and are the results of enormous contributions of the genetic improvement, a condition in which the gains conferred by the genetic breeding tend to reduce.